Natural Fiber Waste from Palm Oil Tree: An Overview of Potential Usage for Indonesia’s Affordable House Building Materials - Widyarko Widyarko; Naresworo Nugroho; Dalhar Susanto (Journal of Architectural Research and Design Studies, 2021)
The palm oil plantation in Indonesia is an overgrowing industry that also poses significant environmental waste problems. The industry produces numerous unused biomass wastes such as EFB (Empty Fruit Bunch), PKS (Palm Kernel Shell), tree trunks, fronds, etc. On the other hand, the national housing backlog number in 2019 had reached 7.6 million units. The government had launched several housing programs to tackle this ever-repeating issue. Yet, all of the plans failed to solve the housing shortage. A new approach is needed to provide a cheap, affordable, and more environmentally friendly affordable house. Previous studies proved that palm oil fiber waste could be altered into building materials such as lumber and other biocomposites like particleboard, fiberboard, plywood, etc. Consequently, by using the construction scheme in the RSH affordable house program released in 2002, palm oil fiber waste should be able to displace conventional wood in most of its parts. That is why there is no reason to halt implementing palm oil fiber waste as building materials, especially to build an affordable house. Therefore, the burden of Indonesia's never-ending housing backlog problems should be eased by converting its over-abundant palm oil fiber waste as its building materials new renewable sources.Keywords: affordable house; alternative materials; bio-composite; palm oil fiber waste